2021
DOI: 10.1080/15548627.2021.1885183
|View full text |Cite
|
Sign up to set email alerts
|

CD36 and LC3B initiated autophagy in B cells regulates the humoral immune response

Abstract: Scavenger receptors are pattern recognition receptors that recognize both foreign and self-ligands, and initiate different mechanisms of cellular activation, often as co-receptors. The function of scavenger receptor CD36 in the immune system has mostly been studied in macrophages but it is also highly expressed by innate type B cells where its function is less explored. Here we report that CD36 is involved in macro-autophagy/autophagy in B cells, and in its absence, the humoral immune response is impaired. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…In contrast, in the same mouse model Lovegrove et al showed that CD36-dependent parasite sequestration affected the accumulation of IgM in BALF as a marker for the development of acute lung injury (ALI) [30]. However, CD36 deficiency may also affect the production of IgM [31]. Furthermore, CD36 also plays a significant role in proinflammatory cytokine responses and Th1 development, which is important for controlling parasite burden [32].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…In contrast, in the same mouse model Lovegrove et al showed that CD36-dependent parasite sequestration affected the accumulation of IgM in BALF as a marker for the development of acute lung injury (ALI) [30]. However, CD36 deficiency may also affect the production of IgM [31]. Furthermore, CD36 also plays a significant role in proinflammatory cytokine responses and Th1 development, which is important for controlling parasite burden [32].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The maintenance of the natural activity of B cells, including the autophagy, contributes to explaining the better immune responses against HIV-1 of LTNP. Confirming this, recent findings highlighted a role for autophagy in B cells in the regulation of humoral immune responses [33]. Overall, despite monocyte/macrophage and B cells representing a restricted percentage of total PMBC, maintenance of high expression of TRIM5α in these particular subsets of cells could be one relevant mechanism for the control of HIV infection observed in LTNP.…”
Section: Discussionmentioning
confidence: 62%
“…As previously mentioned, CD36 is expressed in adipocytes and hepatocytes, but has also been detected in immune cells, such as macrophages and dendritic cells as well as T and B cells (Urban et al, 2001;Corcoran et al, 2002;Won et al, 2008;Couturier et al, 2019). A study published recently by He et al (2021) demonstrated that all peripheral human blood B cell populations express intracellular CD36 except naïve B cells (He et al, 2021). They found that CD36 colocalizes with LC3B upon the induction of autophagy and splenic B cells increase CD36 expression and autophagosome formation after LPS stimulation in vitro.…”
Section: Role Of Cd36 In B Cells In Obesitymentioning
confidence: 92%
“…They found that CD36 colocalizes with LC3B upon the induction of autophagy and splenic B cells increase CD36 expression and autophagosome formation after LPS stimulation in vitro. Interestingly, B cells from CD36 −/− mice have less autophagosome formation upon LPS stimulation (He et al, 2021) and exhibit defects in mitochondrial mobilization and also oxidative phosphorylation (He et al, 2021), as well as, reduced plasma cell formation, subsequent antibody production and proliferation. Remarkably, the expression of CD36 increases in T lymphocytes of adipose tissue and in the liver of mice fed with a HFD, but it is unclear whether it is preferentially expressed by a specific subset of cells (Couturier et al, 2019).…”
Section: Role Of Cd36 In B Cells In Obesitymentioning
confidence: 99%